Civil Liability of an Insolvency Practitioner: Actual Problems - D. O. Yarovoy (Теоретическая и прикладная юриспруденция)
The article is devoted to the consideration of the civil liability of an insolvency administrator in the performance of his duties in the framework of insolvency (bankruptcy) cases. Topical issues related to the civil liability of an insolvency administrator (recovery of damages) are considered. Three issues are identified that stakeholders face in the process of determining, proving and recovering losses. The conclusions about the impact of the mechanism for collecting losses on increasing the efficiency of bankruptcy procedures are summarized.